Focusing on "the important" through targeted NMR experiments: an example of selective 13C–12C bond detection in complex mixtures. (22nd May 2019) - Jenne, Amy; Soong, Ronald; Bermel, Wolfgang; Sharma, Nisha; Masi, Antonio; Tabatabaei Anaraki, Maryam; Simpson, Andre
Abstract : Here, a targeted NMR experiment is introduced which selectively detects the formation of 13 C– 12 C bonds in mixtures. Abstract : Current research is attempting to address more complex questions than ever before. As such, the need to follow complex processes in intact media and mixtures is becoming commonplace. Here, a targeted NMR experiment is introduced which selectively detects the formation of 13 C– 12 C bonds in mixtures. This study introduces the experiment on simple standards, and then demonstrates the potential on increasingly complex processes including: fermentation, Arabidopsis thaliana germination/early growth, and metabolism in Daphnia magna both ex vivo and in vivo . As signals from the intact 12 C and 13 C pools are themselves filtered out, correlations are only observed when a component from each pool combines ( i.e. new 13 C– 12 C bonds) in the formation of new structures. This targeted approach significantly reduces the complexity of the mixtures and provides information on the fate and reactivity of carbon in environmental and biological processes. The experiment has application to follow bond formation wherever two pools of carbon are brought together, be it the incorporation of 13 C enriched food into a living organism's biomass, or the degradation of 13 C enriched plant material in soil.